Toll-like Receptor-4 Activation Boosts the Immunosuppressive Properties of Tumor Cells-derived Exosomes - Domenis, Rossana (Sci Rep, 2019)
The biology of tumor-derived exosomes (TEX) is only partially understood and much remains to be studied in order to define the effect that the tumor microenvironment or the activation of tumor cells exerts on their composition and functions. Increased expression and activity of toll-like receptor 4 (TLR4) in chronic infectious and inflammatory conditions is related with cancer progression: its activation induces an inflammatory signaling that increases the tumorigenic potential of cancer cells promoting their immune evasion. We investigated the immune modulatory properties of TEX released upon cell TLR4 activation, and we found that, although differences were observed depending on the type of the tumor, the treatment influences TEX composition and boosts their immunosuppressive ability. Our results suggest that the activation of TLR4 supports tumor progression by stimulating the release of more effective immunosuppressive exosomes, which allow tumor cells to escape immune surveillance and probably even play a role in the metastatic process.